Studi Literatur: E-Money sebagai Instrumen Kuantitatif dalam Kebijakan Moneter di Indonesia - Meilana Widyaningsih (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Agama Islam Mulia Astuti (STAIMAS) Wonogiri, 2025)
This study aims to examine the application of electronic money (e-money) as a quantitative instrument in monetary policy in Indonesia through a qualitative approach based on literature review. In the digitalization era, the transformation of the payment system has developed rapidly, altering consumption patterns and the structure of the national financial system. This study utilizes various secondary literature sources to evaluate how e-money impacts financial inclusion, consumer behavior, the national payment system, and monetary stability. The findings indicate that e-money holds significant potential in supporting the effectiveness of monetary policy, particularly in expanding the monetary base and contributing to inflation control. However, its effectiveness as a quantitative instrument depends on supervision, regulation, and synergy between monetary authorities and digital financial industry players.